Didactics, methodology, pedagogical technology and modeling of educational and cognitive processes (Pedagogy of Higher and Secondary Education, 2012)
Onopa V. M. Didactics, methodology, pedagogical technology and modeling of educational and cognitive processes.There are given the logic-semantical analysis and the scientific reliability of definitions «didactics», «methodology», «pedagogical technology» in this article. There are disclosed psychologic-pedagogical and methodologic-organizing aspects of technological modeling in it. There are proposed structural-functional models of educational process which must provide the strength of knowledge.
Keywords: didactics; methodology; pedagogical technology; strength of knowledge; educational modeling